Peran Dewan Pengawas Syariah dalam Meningkatkan Tanggung Jawab Sosial Islam : Apakah Ukuran Bank Memiliki Efek Moderasi? - Mauluddi, Hasbi Assidiki; Kristianingsih, Kristianingsih; Setiawan, Setiawan (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
The growth of Islamic banking has increased interest in the practice of Islamic Social Responsibility (ISR) within these financial institutions. The Sharia Supervisory Board (DPS) plays a crucial role in ensuring compliance with Sharia principles and supporting the implementation of ISR. However, how the characteristics of the DPS and the size of the bank moderate this influence is not fully understood. This research aims to investigate the influence of the characteristics of the Sharia Supervisory Board, such as size, age, and meeting frequency, on Islamic Social Responsibility in Islamic banks, and to understand how the size of the bank moderates this influence. This study uses a quantitative method with an associative approach. Secondary data from financial reports and sustainability reports of Islamic banks over the period of 2015-2022 were analyzed using panel data regression with the Random Effect Model. Sample selection was conducted using purposive sampling method with specific criteria to ensure data consistency. The results show that the size of the Sharia Supervisory Board (DPS_SIZE) negatively influences ISR, while the age of the Sharia Supervisory Board (DPS_AGE) positively influences ISR. However, when moderated by the size of the bank (SIZE), the influence of DPS size becomes positive in larger banks, while the age of the DPS has a negative impact. The frequency of DPS meetings (DPS_MEET) generally has a negative effect on ISR, but in larger banks, higher meeting frequency provides more intensive and responsive oversight, thus positively impacting ISR performance. This study highlights the importance of considering the characteristics of the DPS and the size of the bank in optimizing the implementation of ISR in Islamic banks.